MOF-71 SYNTHESIS AS ACTIVE MATERIAL NONENZYMATIC ELECTROCHEMICAL SENSOR FOR URIC ACID DETECTION IN HUMAN BODY - Nur Hakim, Fahmi
The uric acid level in the human body that exceeds the normal limit (0.24-0.42 mM) leads to many diseases such as hyperuricemia, gout, and arthritis. So, measuring uric acid levels is needed regularly to maintain a normal level of uric acid. There are several methods of uric acid measurement such as colorimetric, enzymatic, and electrochemical. Electrochemical methods have been developed to replace colorimetric methods that have poor stability and enzymatic methods that depend on the quality of the enzyme. The electrochemical method was chosen because it measures uric acid with high accuracy with low production costs.